Development of Interactive Multimedia for Introducing Letters and Numbers to Kindergarten Students - Saputra, Hendra Nelva; Said, Hasmira; Sarpina (Jurusan PG-PAUD Universitas Halu Oleo,, 2024)
The aim of this research is to develop interactive multimedia for introducing letters and numbers that can be used in the learning process in kindergartens. This study uses the 4D development model, which includes the stages of define, design, develop, and disseminate. The data collection techniques used in this research are observation and questionnaires. The data analysis was conducted using Likert scale measurements. Overall, the developed interactive learning media has undergone a series of feasibility tests from various aspects, both by media experts and content experts. According to the media experts' assessment, this media obtained an average percentage of 91.67%, which falls into the